Voltage‐activated complexation of α‐synuclein with three diverse β‐barrel channels: VDAC, MspA, and α‐hemolysin. Issue 5 (6th December 2021) - Hoogerheide, David P.; Gurnev, Philip A.; Rostovtseva, Tatiana K.; Bezrukov, Sergey M.
Abstract: Voltage‐activated complexation is the process by which a transmembrane potential drives complex formation between a membrane‐embedded channel and a soluble or membrane‐peripheral target protein. Metabolite and calcium flux across the mitochondrial outer membrane was shown to be regulated by voltage‐activated complexation of the voltage‐dependent anion channel (VDAC) and either dimeric tubulin or α‐synuclein (αSyn). However, the roles played by VDAC's characteristic attributes—its anion selectivity and voltage gating behavior—have remained unclear. Here, we compare in vitro measurements of voltage‐activated complexation of αSyn with three well‐characterized β‐barrel channels—VDAC, MspA, and α‐hemolysin—that differ widely in their organism of origin, structure, geometry, charge density distribution, and voltage gating behavior. The voltage dependences of the complexation dynamics for the different channels are observed to differ quantitatively but have similar qualitative features. In each case, energy landscape modeling describes the complexation dynamics in a manner consistent with the known properties of the individual channels, while voltage gating does not appear to play a role. The reaction free energy landscapes thus calculated reveal a non‐trivial dependence of the αSyn/channel complex stability on the surface density of αSyn.